Peach signal control software is an important part of our lives - Dilobar O’tkirovna Abdullayeva; Miraziz Muxtorovich Ismoilov; Akmal Tulkin ug'li Djurakulov; Nigora Muzaffar qizi Abdieva; Durdona Yodgorbekovna Khasanova (Genius Publishing Group, 2022)
This article introduces voice user interfaces to speech recognition programs, such as voice dialing, for example, "call home", call forwarding, for example, "I want to call", control of domicile devices, keyword search, for example, finding a podcast with specific words, entering simple data, for example, entering a credit card number, preparing structured documents, for example, radiology report, speaker features, speech-to-text processing, for example, word processors or electronic Mail messages and airplanes are usually called direct voice access. Optimal use of high-speed programmable digital signal processors generally demands familiarity with machine architectural features and hence, the production of programs whose structure reflects and exploits those features. In contrast, it is apparent that little effort has been made to develop programming techniques that fully realize the signal processing computational capability of standard minicomputers. In this paper, it is shown that a functional high-level language signal processing program can easily be modified so as to produce a similar program that, when executed, automatically generates another program containing precomputed algorithm sequencing and data access information. The generated program will then utilize central processor arithmetic and logical capability only for data-dependent computation. In this way, instructions normally associated with computation for program sequencing/control or data access are eliminated, and all benefits of increased algorithm complexity for reduction of data-dependent arithmetic computation are in fact realized as decreased program execution time
Keywords: computation; arithmetic; realized; program